Neurinoma in the buccal mucosa - (:unkn) unknown (Journal of Clinical Pediatric Dentistry, 2000)
A 14-year-old girl was referred to our clinic with a problem of a painless slow growing lesion for approximately three years. MR imaging findings of lesion was "retention cyst of the salivary gland". Controversially, the histological examination of the total excised specimen was "nenrinoma " and that was inconsistent with MR findings. Neural tissue tumors of the oral cavity are rare, however, this diagnosis was confirmed by surgical excision and histopathological examination. There was a rare location of the lesion as well.